Evaluation Report on Member of Parliament Local Area Development Scheme - Planning Commission (Planning Commission, 2001)
Member of Parliament Local Area Development Scheme (MPLADS) was introduced in December 1993. The objective is to enable the Members of Parliament (MP) to suggest and get executed developmental works of capital nature based on locally felt needs with emphasis on creation of durable assets. Under this scheme each elected member of Lok Sabha suggests developmental works in his constituency. The elected member of Rajya Sabha can recommend works in any district of his State. A nominated member can suggest work in only one State of his choice. Each MP can recommend to the District Collector developmental works, expenditure on each work generally not exceeding Rs. 10 lakhs (enhanced to Rs.25 lakhs while this study was in progress) up to a total expenditure of Rs. 2 crores every year.
Programme Evaluation Organisation Planning Commission Government of India New Delhi-110001 November, 2001